Truncation on N-Terminal Hydrophobic Domain of L1 Major Capsid Protein of Human Papillomavirus Type 52 Enhances Its Expression in Hansenula polymorpha - Arifah, Rosyida Khusniatul; Firdaus, Moh Egy Rahman; Chairunnisa, Sheila; Irawan, Shasmita; Ekawati, Nurlaili; Irawan, Herman; Nurfatwa, Maritsa; Hertati, Ai; Swasthikawati, Sri; Novianti, Ela; Mustafawi, Wike Zahra; Nur Umami, Rifqiyah; Mustopa, Apon Zaenal (Bogor Agricultural University, Indonesia, 2025)
Human papillomavirus (HPV) infection is the main cause of cervical cancer. The administration of the HPV prophylactic vaccine, which is commonly produced based on HPV L1 major capsid protein, significantly reduces the incidence of cervical cancer. However, the coverage of the HPV vaccination program is often hindered due to its relatively high cost. This study aimed to evaluate the impact of N-terminal hydrophobic domain truncation on the expression of L1 major capsid protein of HPV type 52 in Hansenula polymorpha. The truncation enhanced the yield of L1 protein expression compared with the full length, which was confirmed by Western blot and ELISA. Furthermore, the truncated L1 protein formed virus-like particles (VLPs), which were confirmed by transmission electron microscopy (TEM). Bioinformatics analysis showed that the truncated L1 protein was more soluble compared with the full length, possibly increasing the protein expression. These findings could pave the way for the development of a more cost-effective HPV type 52 L1 protein production in H. polymorpha to be used as a VLP-based prophylactic vaccine.